I’d Like to Speak to the Person in Charge: Measuring Dominant Ethnopolitical Organizations in the Middle East - Petrich, Katharine (Terrorism and political violence, 2024)
Why do some organizations come to represent their communities while others remain footnotes of history? While ethnopolitics exist worldwide, there is no consensus about which organizations “rise to the top” to become the standard bearers for their communities and causes. In the developing world, the answer is often presumed to be the willingness to use violence, exercising territorial control, or securing support from external actors like foreign states. This article tests these assumptions using the Minorities at Risk Organizational Behavior (MAROB) dataset, and finds that contrary to much of the policy literature and popular news media, the factors which predict ethnopolitical organizational dominance are instead the provision of social services, incorporating a gender inclusive ideology, and maintaining clear and consolidated leadership in the form of a single individual. These findings have clear policy implications for both domestic and international engagement with ethnopolitical groups.